Assesment Environmental Sustainability at Upper Watershed Area Based on Bioindicators Knowledge Using The Rapid Appraisal of River Conservation Status (RapRiCons) for Sutainable River Conservation - Rahardjanto, Abdulkadir; Kusnoputranto, Haryoto; Sutjiningsih, Dwita; Seda, Francisia SSE (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green Technology, 2017)
River conservation activity is an activity that must be performed continuously and takes a long period in socio-ecological-economy and politics area. This conservation activity will run well if supported by community’s awareness of this conservation activity. Unfortunately, not every element of society consciously takes part in river conservation activity. Main issue in this research is the presence of people knowledge about bioindicator increase can be used as consciousness leverage in doing river conservation. River conservation that has been recorded by people can be evaluated by developing five dimensions’ measurement which is ecological dimension, economical dimension, technological dimension, socio-cultural dimension, and ethical dimension that summarized in evaluation tool called The Rapid appraisal of River Conservation Status (RapRiCons) which is an evaluation tool for environment sustainability. This tool is a modification from RAPFISH. This research used quantitative approach with descriptive analytic method. The results and conclusions from this research show that environment sustainability that revealed in five measurement, all shows that good scores and shows enough environment sustainability status. The result from this research can be used as reference about strength and weakness on each measurable dimension as bioindicator based river conservation evaluation that performed independently by community